Influence of in situ phase formation on properties of calcium zirconate refractories. Issue 1 (January 2017) - Schafföner, Stefan; Fruhstorfer, Jens; Faßauer, Christina; Freitag, Lisa; Jahn, Constantin; Aneziris, Christos G.
Abstract: This study investigates chemical, physical, mechanical, and thermomechanical properties of calcium zirconate (CaZrO3 ) refractories. The applied fused raw material contained some residual cubic zirconia, which impairs the corrosion resistance of CaZrO3 refractories. To adjust the stoichiometry, CaCO3 was added. Furthermore, stoichiometric amounts of CaCO3 /monoclinic ZrO2 were added to promote an in situ pore formation without altering the phase composition. After firing cubic zirconia was only found in the coarse grained aggregates. CaCO3 additions increased the apparent porosity and reduced the thermal expansion coefficient due to the stoichiometric adjustment. Surprisingly, a higher porosity did not result in an improved thermal shock resistance, which can be attributed to a shift to larger pore sizes. This might cause a lower crack density, which is usually associated with a reduced thermal shock resistance. Future work will address the formation of smaller pores and the evaluation of the thermal shock resistance under practical conditions.